2018
DOI: 10.1002/14651858.cd011977.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Blue-light filtering intraocular lenses (IOLs) for protecting macular health

Abstract: This systematic review shows with moderate certainty that there is no clinically meaningful difference in short-term BCVA with the two types of IOLs. Further, based upon available data, these findings suggest that there is no clinically meaningful difference in short-term contrast sensitivity with the two interventions, although there was a low level of certainty for this outcome due to a small number of included studies and their inherent risk of bias. Based upon current, best-available research evidence, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 118 publications
1
46
0
1
Order By: Relevance
“…The impetus to develop an IOL that filters blue light came from an appreciation that the higher energy of short wavelength light may be phototoxic and damage the retinal pigment epithelium, thereby accelerating the progression of ocular diseases, such as age-related macular degeneration ( Downie et al., 2018 ; Pollack et al., 1996 ; Wang et al., 2003 ). However, a recent systematic review concluded that the practice of using BF-IOL for retinal protection is not supported by the best available evidence ( Downie et al., 2018 ). A recent survey of Australian ophthalmologists reported that half of surgeons do not recommend BF-IOL, and of those who do, the most frequent reason was as a general safety measure against blue light ( Singh et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impetus to develop an IOL that filters blue light came from an appreciation that the higher energy of short wavelength light may be phototoxic and damage the retinal pigment epithelium, thereby accelerating the progression of ocular diseases, such as age-related macular degeneration ( Downie et al., 2018 ; Pollack et al., 1996 ; Wang et al., 2003 ). However, a recent systematic review concluded that the practice of using BF-IOL for retinal protection is not supported by the best available evidence ( Downie et al., 2018 ). A recent survey of Australian ophthalmologists reported that half of surgeons do not recommend BF-IOL, and of those who do, the most frequent reason was as a general safety measure against blue light ( Singh et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…BF-IOL, in addition to UV, also impede the transmission of the lower visible blue spectrum between 400 and 500 nm ( Brockmann et al., 2008 ). This technological advancement developed from an appreciation that the higher energy of short wavelength light may be phototoxic and damage the retinal pigment epithelium, thereby accelerating the progression of ocular diseases, such as age-related macular degeneration ( Downie et al., 2018 ; Pollack et al., 1996 ; Wang et al., 2003 ). This variation in practice and spectral properties of implanted IOLs lends itself to a natural experiment to explore the ramifications of restoring exposure to blue light (i.e., implantation of conventional IOL) or continued loss of blue light (i.e., implantation of BF-IOL) on the long-term health outcomes of patients undergoing bilateral cataract surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, a very recent systemic review concluded that there was still unclear regarding the protective function of blue light-filtering intraocular lenses on macular health or the reduced risk associated with the development or progression of AMD. 38 Other studies suggested that mechanisms underlying the significant relationship between cataract surgery and AMD could be the intraoperative photic damage caused by the operating microscope. 39 Further research is needed to clarify possible mechanisms underlying the significant association between cataract surgery and AMD, if this significant association is confirmed in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…B. die Aussage, ein unterschwelliger Nanosekundenlaser könne die neovaskuläre Makuladegeneration „ verhindern “ [ 39 ], jede Katarakt mĂĽsse „so frĂĽh wie möglich“ operiert werden [ 40 ], die Vitreolyse garantiere das „ vollständige Verschwinden “ von TrĂĽbungen [ 41 ] oder diffraktive bzw. gelbe Linsen versprächen „ eine bessere Abbildungsqualität “ [ 42 , 43 ]. Weil aktuell mit der höchsten Evidenzstufe weder genereller Vorteil noch Nutzen der Kataraktoperation mittels Femtosekundenlaser gefunden wurde [ 44 ], ist es falsch, ein steinzeitlich verzerrtes Gegenbild der konventionellen Chirurgie beispielsweise mit der Verwendung eines groben und ungenauen „Skalpells“ zu konstruieren.…”
Section: Diskussionunclassified